PEDAGOGICAL CONDITIONS OF CREATIVE FORMATION PERSONALITIES OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2006)
The article deals with higher educational process of teaching with due regard for objective and subjective conditions of future teachers training Special attention is given to intensification of motivation in teaching, emotional value of the future profession, substantial and technological renovation in teaching.